Urban Traffic Control via Planning with Global State Constraints (Extended Abstract) - Ivankovic, Franc; Vallati, Mauro; Chrpa, Lukáš; Roveri, Marco (Proceedings of the International Symposium on Combinatorial Search, 2022)
Planning with global state constraints is an extension of classical planning such that some properties of each state are derived via a set of rules common to all states. This approach is important for the application of planning techniques in manipulating cyber-physical systems, and has been shown to be effective in practice. Urban Traffic Control (UTC) deals with the control and management of traffic in urban regions, and includes the optimisation of traffic signals configuration to minimise traffic congestion and travel delays. In this paper, we briefly introduce how to cast the UTC problem into the formalism of planning with global state constraints, and we perform a preliminary experimental evaluation considering significant scenarios taken from the literature, and a new one based on real-world data. The results show that the approach is feasible, and the quality of generated solutions has been confirmed in simulation using existing symbolic models.